THE MONASTERIES OF METEORA DURING THE OTTOMAN PERIOD AND THE PRACTICE OF MONASTIC CONFINEMENT - Bayraktar-Tellan, Elif (Analecta Stagorum et Meteororum, 2022)
Monastic confinement as a disciplinary measure had a long past in the Christian tradition and continued to be implemented by the Constantinopolitan patriarchs during the Ottoman period. Although our knowledge of the earlier centuries is limited, there is more information on the eighteenth- and the nineteenth-century cases of monastic exile, mainly thanks to the kalebend registers, as well as other relevant Ottoman documentation. The surge of evidence is perhaps related to the increasing role of the Patriarchate of Constantinople during the eighteenth century in matters related to the Greek Orthodox subjects vis-à-vis the Ottoman administration. By this time, monastic confinement was implemented within the Ottoman legal framework of banishment. Besides Mount Athos, the monasteries of Varlaam and Great Meteoro were also major locations of monastic confinement. Apart from the documents of the Ottoman central bureaucracy, monastic archives can also contribute to our insights on the implementation of confinement in collaboration with the Ottoman administration during this period. In this sense, the cases of monastic confinement shed light on a relatively obscure aspect of the Orthodox experience under Ottoman rule.